Protein kinase C promotes restoration of calcium homeostasis to platelet activating factor-stimulated human neutrophils by inhibition of phospholipase C - Anderson Ronald; Pretorius Lynette; Cockeran Riana; Steel Helen C; Theron Annette J; Tintinger Gregory R (BMC, 2009)
Abstract Background The role of protein kinase C (PKC) in regulating the activity of phospholipase C (PLC) in neutrophils activated with the chemoattractant, platelet-activating factor (PAF, 20 and 200 nM), was probed in the current study using the selective PKC inhibitors, GF10903X (0.5 - 1 μM) and staurosporine (400 nM). Methods Alterations in cytosolic Ca2+, Ca2+ influx, inositol triphosphate (IP3), and leukotriene B4 production were measured using spectrofluorimetric, radiometric and competitive binding radioreceptor and immunoassay procedures, respectively. Results Activation of the cells with PAF was accompanied by an abrupt increase in cytosolic Ca2+ followed by a gradual decline towards basal levels. Pretreatment of neutrophils with the PKC inhibitors significantly increased IP3 production with associated enhanced Ca2+ release from storage vesicles, prolongation of the peak cytosolic Ca2+ transients, delayed clearance and exaggerated reuptake of the cation, and markedly increased synthesis of LTB4. The alterations in Ca2+ fluxes observed with the PKC inhibitors were significantly attenuated by U73122, a PLC inhibitor, as well as by cyclic AMP-mediated upregulation of the Ca2+-resequestering endomembrane ATPase. Taken together, these observations are compatible with a mechanism whereby PKC negatively modulates the activity of PLC, with consequent suppression of IP3 production and down-regulation of Ca2+ mediated pro-inflammatory responses of PAF-activated neutrophils. Conclusion Although generally considered to initiate and/or amplify intracellular signalling cascades which activate and sustain the pro-inflammatory activities of neutrophils and other cell types, the findings of the current study have identified a potentially important physiological, anti-inflammatory function for PKC, at least in neutrophils.